Improving the Efficacy of English Instruction at Qawmi Madrasas (Islamic Seminaries) in Bangladesh. (May 2020) - Golam, Azam Md; Kusakabe, Tatsuya
This study examined English teaching and learning (Grade 8 level) in Qawmi Madrasa schools, which are not recognized by the Bangladeshi government's Education Department. The study investigated the improvements needed in Qawmi Madrasas English teaching programs to enable students to secure public university admission and Bangladeshi civil service positions. We conducted ethno-methodological surveys in 2018 with the students, teachers, and principals of eight Qawmi Madrasas in the south-central and southeastern areas of Bangladesh. The study found that the environment in Qawmi Madrasas in the south-central region was not conducive to English learning, in contrast to the situation in the southeastern region. In addition, teacher salaries and other resources were inadequate in the south-central region in comparison to the southeastern region. In the south-central region, the student interviewees commented that classroom resources, that is, English textbooks, should be more effectively implemented. The findings of this research also indicate an urgent need for teacher training in English-language learning in the south-central region to develop teachers' skills in teaching methodologies and strategies.